Interpretative Analysis and Testing Statistics to test questions testing the Mobile Government questionnaire against the model of readiness and successful adoption, - M. S, Hartawan; I, Mantra; I. W., Widi Pradnyana (2019)
In Mobile Government Research is increasingly developing in the era of information that is very quickly accessible to employees in the achievement of information. The purpose of this study is at the level of readiness and success of mobile government users through analysis. Research questionnaires about the mobile government that will be obtained will be analyzed using SMARTPLS 2. which includes testing. This research produces interpretive data to confirm the results of statistical analysis in testing the cellular government questionnaire. The results of this study are expected to be a reference and literature for the government in developing cellular governance and can provide solutions for further development of cellular governance. From the results of this study, 67% of respondents have the ability to use mobile at the level of 81-100%. and 63% of respondents stated that the position is very ready to use the mobile government (m-Gov).